A praça João Pinheiro: cidade, memórias e viver urbano - Pouso Alegre, 1941-1969 - Ishimura, Juliano Hiroshi Ikeda (2008)
In dissertation intitled The Plaza João Pinheiro: city, memory and live urban.Pouso Alegre city, 1941-1969. sews together a reflection about the urban interventions of significant impact, in the Plaza João Pinheiro, became the theme for the development of this research project. The many histories and memories recounted in interviews with users, passers-by, and the city s public sector representatives, interwoven with other documents both written as the press, the act of Municipal Chamber and written-memory reveal the varied meanings the plaza, has had for the city and your s everyday life. Fundamental to this study are the effects of this intervention on the way of to see and living with the plaza as a space. I searched therefore establish a continuous dialogue with different kinds of legal, whose objective of making up a multi-faced history of that territory, able to desconstruct the several images that were attached to the Plaza, with its own rules and values. A culture of health and infancy it marked the Plaza João Pinheiro and its outskirts. The weight of hygienist ideas the repression of feminine sexuality and the ideological manipulations show that such institutions as the Infantile Parks and the Dispensaries they are more of the one than leisure and learning places, they are local of disciplines and reclusion. Replete of social disputes and alliances, the research, divided in three parts, besides disclosing and feelings, some of which cannot be seen in the daily life of the city nowadays. The first part searched deals with the process of occupation and building of Plaza João Pinheiro, which was done in the beginnings of the XX century. Another one of the moments was the proposal and installation of the Infantile Park Major Dornelles , in the first half of the 1940 s. For the last on it was I looked for to examine the process of establishing the bus station and the town hall headquarter in the final years 1960 s